The Forensics Artifacts on Remote Desktop Protocol and Service: Talha Ashfaq, Muhammad Shairoze Malik - Talha Ashfaq; Muhammad Shairoze Malik (International Journal for Electronic Crime Investigation, 2022)
Remote Desktop Protocol provides users with a graphical user interface to access the system remotely and its implementation is called “remote desktop services”. This is widely used by network administrators and remote workers. Due to vulnerabilities and weak configurations, the protocol is hugely abused by threat actors and hackers to perform malicious acts such as data infiltration, deploying backdoors, malware, and lateral movements. In this article, there will be a discussion on the importance of RDP in digital forensics, understanding RDP-based artifacts and there use in forensics investigations where RDP was suspected to be involved.